PENGARUH LEMBAR KERJA SISWA(LKS) BERBASIS SCIENTIFIC REASONING PADA MATERI RANGKAIAN ARUS SEARAH TERHADAP HASIL BELAJAR FISIKA SISWA DI SMK - Diah Pratiwi; Bambang Supriadi; Subiki Subiki (JURNAL PEMBELAJARAN FISIKA, 2019)
In the 2013 curriculum, there is a need for learning resources that fit the demands of the curriculum by considering the needs of students such as LKS. Physics learning sometimes lacks the ability to think or reason so that the learning outcomes of physics are still low. Therefore it is necessary for Student Worksheets (LKS) that can train scientific reasoning (Scientific Reasoning) to improve students' physics learning outcomes in Vocational High Schools. The research objectives were: (1) Assessing the learning outcomes of vocational physics students after using worksheets based on scientific reasoning on Direct Current Circuits, (2) Knowing how much students respond to Student Worksheets (LKS) based on scientific reasoning on Direct Current Circuits. This research used the Pretest Posttest Control Group Design research design, by giving the pretest and posttest questions in the control class and the experimental class. Based on the results of the research showed that after learning using Scientific Reasoning based worksheets on the experimental class experienced a significant increase from the initial average value of 28.8462 increasing to 84.1667Key Word : Learning Achievement , Scientific Reasoning, Student worksheet